2021
DOI: 10.1108/josm-12-2020-0447
|View full text |Cite
|
Sign up to set email alerts
|

How industry and occupational stereotypes shape consumers' trust, value and loyalty judgments concerning service brands

Abstract: PurposeLongitudinal studies have shown that consumer satisfaction has increased over the last 15 years, whereas trust and loyalty have decreased during the same period. This finding contradicts the trust–value–loyalty model (TVLM), which posits that higher satisfaction increases consumers' trust, value and loyalty levels. To explain this counterintuitive trend, this study draws on models of trust formation to integrate the stereotype content model and the TVLM. It argues that consumers' occupational and indust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 106 publications
(169 reference statements)
0
16
0
1
Order By: Relevance
“…Patient loyalty, a behavioral intention or action to repurchase a preferred product or service consistently, is regarded as a key element of the business success of healthcare service providers [ 1 – 25 ]. In recent years, the Chinese government has gradually privatized healthcare services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient loyalty, a behavioral intention or action to repurchase a preferred product or service consistently, is regarded as a key element of the business success of healthcare service providers [ 1 – 25 ]. In recent years, the Chinese government has gradually privatized healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that health services in China are undergoing privatization, this study explores the effects and influence paths of service quality, brand image, perceived value, and service satisfaction on outpatients’ loyalty to China’s private dental clinics. This study aims to make a contribution in the literature discussing trust-value-loyalty model (TVLM) [ 25 ] and customers in the private health service agencies. In addition, the findings of this study contribute to improving the outpatients’ loyalty in China’s private dental clinics.…”
Section: Introductionmentioning
confidence: 99%
“…However, longitudinal and multiindustry surveys show that while customer satisfaction has increased over the past 15 years (American Customer Satisfaction Index, 2019), consumers' trust (Edelman, 2020;Rajavi et al, 2019) and loyalty (Dawes et al, 2015;Evanschitzky et al, 2020) levels have decreased. We now recognize that there is a need to investigate factorsother than their satisfaction -that influence consumers' trust (Gidakovic and Zabkar, 2021). Our results may also be helpful to policymakers and managers in a wide range of industries especially the banking industry, prompting them to adopt approaches and strategies designed to increase consumers' trust and frontline employees' performance.…”
Section: Introductionmentioning
confidence: 83%
“…, 2020) levels have decreased. We now recognize that there is a need to investigate factors – other than their satisfaction –that influence consumers' trust (Gidakovic and Zabkar, 2021). Our results may also be helpful to policymakers and managers in a wide range of industries especially the banking industry, prompting them to adopt approaches and strategies designed to increase consumers' trust and frontline employees' performance.…”
Section: Introductionmentioning
confidence: 99%
“…8 Prior studies have revealed that customer satisfaction positively influences customer loyalty. [34][35][36][37][38] In the online market, if customers are satisfied with a transaction, they perceive that they are getting a greater value than they would get from the online retailer's competitor. 39 Further, they will be more likely to come back to the online retailer's website and make a purchase again and to recommend the online retailer to other potential customers.…”
Section: Research Frameworkmentioning
confidence: 99%